Perilaku UMKM Terhadap Pelaksanaan Pemungutan Pajak UMKM Dengan Menggunakan Self Assessment System - Eka Dyah Setyaningsih; Mugi Harsono (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2021)
Abstract - The implementation of MSME tax collection with the Self Assessment System is a tax collection system by calculating, paying and reporting by yourself by giving confidence to taxpayers based on applicable laws and regulations. This study aims to 1) determine the implementation of the implementation of the self-assessment system in Makasar District, East Jakarta; 2) analyzing the understanding of the taxation knowledge of the UMKM taxpayers, 3) analyzing the implementation of the MSME taxpayer obligations 4) analyzing the tax awareness of taxpayers' sensitivity. This type of research is qualitative descriptive by means of direct primary data collection through interviews with 10 taxpayer informants of MSME actors. The results of his research indicate that the implementation of the self-assessment system has not been going well and more intensive assistance is needed. This is due to the lack of public awareness of taxation and lack of understanding of taxation knowledge. There are 4 informants who run the self-assessment system, 2 of which are assisted by tax consultant services and 6 other informants have not implemented the self assetment system properly